2020
DOI: 10.1177/1352458520921087
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of cladribine for Australian patients with multiple sclerosis: An MSBase registry substudy

Abstract: Background/objective: Observational clinical data from cladribine-treated patients with relapsing forms of multiple sclerosis (MS) were recorded in the Australian MS registry powered by the MSBase registry platform (5-year follow-up) and analysed to complement information from the pivotal cladribine clinical trials in MS. Methods: A cohort of 90 cladribine-treated patients with follow-up data reported by treating physicians and recorded in the Australian MSBase registry (database lock February 2016) were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 32 publications
1
33
0
1
Order By: Relevance
“…Indeed, in a recent analysis of patients who received one course of cladribine in the International MSBase registry, almost three quarters of patients who switched from cladribine tablets to another DMD did so before a relapse. 18 However, from CLARITY Extension it is now known that the clinical efficacy of cladribine tablets lasts beyond the initial reduction and recovery of total lymphocyte counts to the normal range. 3 Despite the lack of guidance on situations when patients might need additional DMD treatment following cladribine tablets, it is notable that over 30% of patients did not receive another DMD after receiving cladribine tablets in the clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent analysis of patients who received one course of cladribine in the International MSBase registry, almost three quarters of patients who switched from cladribine tablets to another DMD did so before a relapse. 18 However, from CLARITY Extension it is now known that the clinical efficacy of cladribine tablets lasts beyond the initial reduction and recovery of total lymphocyte counts to the normal range. 3 Despite the lack of guidance on situations when patients might need additional DMD treatment following cladribine tablets, it is notable that over 30% of patients did not receive another DMD after receiving cladribine tablets in the clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence gathered can be used to guide treatment decisions [17]. For cladribine tablets, real-world effects were shown in an Australian MSBase registry study, which reported an ∼80% progressionfree (measured on the Expanded Disability Status Scale [EDSS]) rate and a 65% relapse-free rate after 2 years of treatment [19]. Long-term benefits were recently reported in two studies of Italian patients who participated in the RCTs (CLARITY, CLARITY Extension, ORACLE-MS or ONWARD).…”
Section: Cladribine Tabletsmentioning
confidence: 99%
“…Given the high prevalence of MS in the USA [4], more studies are needed to evaluate the effect of cladribine tablets in US patients with MS. To date, there have not been any completed studies on cladribine tablets based solely in the US. The majority of study sites for the Phase III CLARITY and ORACLE-MS trials and all the sites for the completed follow-up studies of patients were located outside of the US [13,[19][20][21]27]. While CLOCK-MS and CLADRINA are US-based studies, these studies have a smaller participant population at ≤50 per study [25,26].…”
Section: Lack Of Real-world Data On Cladribine Tablets In the Usmentioning
confidence: 99%
“…Observational data from the Australian registry MS base 32 including 87 patients with heterogeneous baseline characteristics indicate sustained efficacy of oral cladribine after only one treatment cycle (in these patients, the second cycle in year 2 had been omitted due to a temporary suspension of the drug license). Among the 66 patients in whom EDSS follow-up data were available, approximately 80% remained free of EDSS progression and 65% were free of relapses within the first 2 years after completing a single cycle of oral cladribine.…”
Section: Available Evidencementioning
confidence: 99%
“…However, available evidence is currently limited to case series from cohort studies and data from MS registries. 32 Alemtuzumab and other immune cell-depleting antibodies should be used with caution after oral pulsed therapy with cladribine tablets and should at least be withheld until lymphocyte counts approach normal levels.…”
Section: Available Evidencementioning
confidence: 99%